The Beveridge report and the health services
1943 1943 1940s 2 pages account of means or social position. Health is an asset to the State and it is in the interest of the State and of every individual that the health of all should be kept at its highest level. A Practical Scheme. What Sir William Beveridge describes in general terms, "a health service which will ensure that for every citizen there is available whatever medical treatment he requires, in whatever form he requires it, domiciliary or institutional, general, specialist or consultant, and will ensure also the provision of dental, ophthalmic and surgical appliances, nursing and midwifery and rehabilitation after accidents," has to be translated into practical terms, into doctors, hospitals, nurses and all other health workers. How is this to be done? Firstly by a nationally planned service, under the general control of the Minister of Health who should be responsible to Parliament. Secondly by dividing the country into areas, each of which should be large enough to be able to support economically (with whatever assistance is needed from national funds in the case of poor areas), and to keep fully occupied a medical service complete in itself; the whole to be administered by a local authority elected for the area. Thirdly by establishing "Health Units" within each area as the actual operational unit of the health service. To the worker and the doctor alike it is this "Health Unit" which is of the utmost importance as on it depends the type of service the citizen will get. An ideal size is a district with a population of 100,000 people. The medical service should be provided by and through groups of general practitioners working at fully-equipped Health Centres. These should be linked with each other and with the Health Unit Hospital, which modern science dictates should be wherever possible a large General Hospital, able to provide a complete service of specialists and consultants, all of whom would be available in the homes and at the Centres on the call of the general practitioner, or Home Doctor as some prefer to call him. With the medical profession would be linked all the nurses, health visitors, social welfare workers, home helps, etc., that go to make up a modern health system. And the services of all should be available without any question of fee, whenever required; the doctors and other health workers would be salaried officers working under the best conditions and while they would have their leisure hours as does every other worker, the service as a whole would be constantly available, ready to serve by day and night, in sickness or in health, so as to build up a nation that would be able to enjoy and to increase all the good things of the earth. The health service described in outline above is the form of health service and is the policy of the SOCIALIST MEDICAL ASSOCIATION (the association of socialist health workers) The S.M.A.'s policy is described in detail in The Socialist Programing for Health (price 4d.) obtainable from The Socialist Medical Association, 33 Murray Road, Northwood, Mddx. 643065 — HURLEY'S. THE RITHERDON PRESS. S.W.17 126/TG/377/1/1/123